CSR EFFECT ON MARKET AND FINANCIAL PERFORMANCE - Dewi, Dian Masita (El Dinar: Jurnal Keuangan dan Perbankan Syariah, 2013)
This study aims to predict causality model [33] effect of Corporate Social Responsibility on financial performance. This study also examines motivation of CSR implementation based on financial performance and market performance in non-financial public companies and banks that disclose CSR activities and listed at Indonesia Stock Exchange during 2007â€“2009. Numbers of samples were 46 companies. Data was analyzed by GSCA. Research result showed that there was a significant direct effect between CSR on Return on Assets (ROA), Return on Equity (ROE). In contrast, there was no significant direct effect between CSR on Market Value Added (MVA). In addition, there was a significant direct effect between Return on Assets (ROA) on CSR, Return on Equity (ROE) on CSR and there was no significant direct effect between Market Value Added (MVA) on CSR. There were three empirical findings novelties of this study. First, return on assets (ROA) has positive effect on CSR and otherwise CSR has positive effect on ROA. Second, ROE has positive effect on CSR and otherwise CSR has positive effect on ROE. Last, MVA affect on CSR and otherwise CSR affect on MVA. Â